Biomimetic component coating on 3D scaffolds using high bioactivity of mesoporous bioactive ceramics - Yun HS (Dove Medical Press, 2011)
Hui-suk Yun1, Sang-Hyun Kim2, Dongwoo Khang3, Jungil Choi4, Hui-hoon Kim2, Minji Kang31Functional Materials Division, Korea Institute of Materials Science, Gyeongnam, Korea; 2Department of Pharmacology, School of Medicine, Kyungpook National University, Jung-Gu, Daegu, Korea; 3School of Nano and Advanced Materials Science and Engineering and Center for NMBE, Gyeongsang National University, Jinju, Korea; 4Department of Anatomy, Institute of Health Science and School of Medicine, Gyeongsang National University, Jinju, Gyeongnam, KoreaBackground: Mesoporous bioactive glasses (MBGs) are very attractive materials for use in bone tissue regeneration because of their extraordinarily high bone-forming bioactivity in vitro. That is, MBGs may induce the rapid formation of hydroxy apatite (HA) in simulated body fluid (SBF), which is a major inorganic component of bone extracellular matrix (ECM) and comes with both good osteoconductivity and high affinity to adsorb proteins. Meanwhile, the high bioactivity of MBGs may lead to an abrupt initial local pH variation during the initial Ca ion-leaching from MBGs at the initial transplant stage, which may induce unexpected negative effects on using them in in vivo application. In this study we suggest a new way of using MBGs in bone tissue regeneration that can improve the strength and make up for the weakness of MBGs. We applied the outstanding bone-forming bioactivity of MBG to coat the main ECM components HA and collagen on the MBG-polycarplolactone (PCL) composite scaffolds for improving their function as bone scaffolds in tissue regeneration. This precoating process can also expect to reduce initial local pH variation of MBGs.Methods and materials: The MBG-PCL scaffolds were immersed in the mixed solution of the collagen and SBF at 37°C for 24 hours. The coating of ECM components on the MBG-PCL scaffolds and the effect of ECM coating on in vitro cell behaviors were confirmed.Results: The ECM components were fully coated on MBG-PCL scaffolds after immersing in SBF containing dilute collagen-I solution only for 24 hours due to the high bone-forming bioactivity of MBG. Both cell affinity and osteoconductivity of MBG-PCL scaffolds were dramatically enhanced by this precoating process.Conclusion: The precoating process of ECM components on MBG-PCL scaffold using a high bioactivity of MBG was not only effective in enhancing the functionality of scaffolds but also effective in eliminating the unexpected side effect. The MBG-PCL scaffold-coated ECM components ideally satisfied the required conditions of scaffold in tissue engineering, including 3D well-interconnected pore structures with high porosity, good bioactivity, enhanced cell affinity, biocompatibility, osteoconductivity, and sufficient mechanical properties, and promise excellent potential application in the field of biomaterials.Keywords: biomimic, mesoporous, ECM components, scaffold, bone regeneration